BECOMING INDONESIAN MOSLEM PARENTS IN DIGITAL AGE : STUDY OF @parentingmuslimid’s POSTS - Lestari, Yuli Ika (Proceeding International Seminar of Islamic Studies, 2023)
Digital age emerged the use of social media as one of major source of information, including Moslem families to access the parenting advices on Instagram.  The study discusses the identities represented on @parenting_islam.id on Instagram.  The objectives of the research were to find out :(1) the strategies of forming Islamic identities in the posts of @parenting_muslim.id and (2) the negotiated and adapted identities represented of the posts by using the Islamic parenting perspective. Qualitative method of the study gathered the data by observing selected posts of account @parenting_muslim.id through physical structure and the descriptive structure of the posts. The first result indicates that the identities as a Moslem represented into strategies to develop positive Islamic identities as parents, particularly in relation to mother-father’s role, the do and don’ts advice, and daily lives motivational posts. Secondly, the negotiated and adapted through the contents were reflected  in  the way to communicate to audiences.   Dynamically  contested nature in the form of Islamic identities come to the fore which are used to demonstrate the value of incorporating Islamic representations into Moslem’s parents as social identity and self-categorisation. This demands a critical review of the importance of representations in the construction of Moslem family’s identity.